I can take it from here: a memoir of trauma, prison and self-empowerment - Forbes, Lisa (Steerforth Press/Truth to Power Books, 2022)
book 1. Chicago: Jump ; Friendly ghosts ; Wiggling ; The Lake Michigan high-rises ; The first time ; Shame ; Mama and Daddy ; Sisters and brothers ; I need a knife ; Mount Olympus ; Romance ; Shunned ; In the loop ; James ; The American dream ; The crime ; Confession ; Cook County Jail ; The trial ; Shipment ; "You just have to be patient" ; Tango aftermath ; Recovery ; The education of Lisa Forbes ; The parable of the enlightened man ; Of thee I sing ; Baptism ; Home ; Prison action committee ; Legacy theatre ; My day -- book 2. Atlanta: New car, new home, new life ; Free ; Entrepreneur ; Marrying Mommy ; Answered prayer ; Really old hurts ; Surgery ; Divorce -- book 3. Colorado: Denver ; A temporary life ; Parliament ; InTown suites ; Zoe ; A room full of faces ; Armageddon ; Lisa Forbes Inc. -- book 4. The way forward: From invisible to restored.